2006
DOI: 10.1007/s10591-006-9009-8
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and Family Therapy Students’ Change in Multicultural Counseling Competencies after a Diversity Course

Abstract: Attention to diversity is required in Commission on Accreditation for Marriage and Family Therapy Education-accredited programs, yet not much research exists regarding the effectiveness of graduate training on therapists' multicultural counseling competencies. In this study, 12 students enrolled in a masters-level diversity class were given pre-and post-tests of their multicultural counseling competencies. Results showed that students significantly increased their multicultural awareness, knowledge, and skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…1 While a variety of scales have been used in evaluating the effects of diversity training (e.g., Multicultural Counseling Inventory (MCI), Attitudes Towards Inclusive Education scale (ATIES), we found that some studies used scales such as the Multicultural Awareness, Knowledge, and Skills Survey (MAKSS; D'Andrea, Daniels, & Heck, 1991) designed to examine awareness of one's attitudes toward ethnic minorities, knowledge concerning minority populations, and cross-cultural communication skills, and the Modern Racism scale (McConahay, 1981) used to assess explicit racial attitudes. For instance, the MAKSS scales were used in six studies in our review-most showing a positive change in cognitions, attitudes, and behaviors (Abernethy, 2005;D'Andrea et al, 1991;Diaz-Lazaro & Cohen, 2001;Guy-Walls, 2007;Murphy, Park, & Lonsdale, 2006;Robinson & Bradley, 1997). Further, it seems variables such as immediate response, awareness, behavior and attitude change have received the most attention in empirical research on diversity training (for exceptions see Dobbin et al, 2006;Ely, 2004a;Kellough & Naff, 2004;Naff & Kellough, 2003).…”
Section: Not Specified 106mentioning
confidence: 99%
See 2 more Smart Citations
“…1 While a variety of scales have been used in evaluating the effects of diversity training (e.g., Multicultural Counseling Inventory (MCI), Attitudes Towards Inclusive Education scale (ATIES), we found that some studies used scales such as the Multicultural Awareness, Knowledge, and Skills Survey (MAKSS; D'Andrea, Daniels, & Heck, 1991) designed to examine awareness of one's attitudes toward ethnic minorities, knowledge concerning minority populations, and cross-cultural communication skills, and the Modern Racism scale (McConahay, 1981) used to assess explicit racial attitudes. For instance, the MAKSS scales were used in six studies in our review-most showing a positive change in cognitions, attitudes, and behaviors (Abernethy, 2005;D'Andrea et al, 1991;Diaz-Lazaro & Cohen, 2001;Guy-Walls, 2007;Murphy, Park, & Lonsdale, 2006;Robinson & Bradley, 1997). Further, it seems variables such as immediate response, awareness, behavior and attitude change have received the most attention in empirical research on diversity training (for exceptions see Dobbin et al, 2006;Ely, 2004a;Kellough & Naff, 2004;Naff & Kellough, 2003).…”
Section: Not Specified 106mentioning
confidence: 99%
“…Yet, in other organizations, the goals of diversity training can be much broader, and training may be conducted as part of a systematic and planned organizational development effort (Bendick, 2001). Paralleling those trends in educational settings, some authors have discussed an infused curriculum approach with an emphasis on diversity across a variety of domains (supervision, coursework, research/writing), whereas others have supported a single-course approach that allows for specific time to attend to the complexity of cases that diversity naturally evokes (Murphy et al, 2006).…”
Section: Training Approach: Stand-alone Versus Integrated Diversity Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Murphy, Park, and Lonsdale (2006), multicultural competency was measured before and after a course was completed in an MFT program. The course selected by Murphy et al (2006) used a variety of training methods, consistent with the tripartite multicultural competence model of awareness, knowledge, and skills discussed earlier.…”
Section: A Training Modelsmentioning
confidence: 99%
“…The course selected by Murphy et al (2006) used a variety of training methods, consistent with the tripartite multicultural competence model of awareness, knowledge, and skills discussed earlier. Students were instructed to create a genogram, engage in class participation regarding assigned readings, and journal reactions to in-class discussions or readings.…”
Section: A Training Modelsmentioning
confidence: 99%